Vulvar Epidermoid Cyst and Type 2 Radical Genital Mutilation - Ozer Birge; Ertugrul Gazi Ozbey; Deniz Arslan; Mustafa Melih Erkan; Feyza Demir; Utku Akgor (Hindawi Limited, 2015)
About 100 million women are estimated to be circumcised globally. Various rates of complications have been encountered, especially after circumcision, such as bleeding, infection, shock, menstrual irregularity, difficulty in urination or common urinary tract infections, inguinal pain, difficulty in sexual intercourse, and genital circumcision scar especially at the vulvar region, and cystic or solid character mass in short and long term. Furthermore, the maternal-fetal morbidity and mortality increase due to bleeding and fistula, which develop after prolonged labor, travail, and difficult labors. Our aim in this paper was to discuss a 42-year-old multiparous female case who had undergone type 2 radical genital mutilation (circumcision) when she was 7 years of age, along with the literature, which has been evaluated for the gradually growing mass at the left inguinal canal region in the last 10 years and diagnosed as epidermoid inclusion cyst developing secondary to postcircumcision surgical ground trauma, since there was no other case found in the literature search that had been circumcised at such an early age and developing after circumcision at such advanced age, and, therefore, this is suggested to be the first case on this subject.